Characterization and compensation of f0 inhomogeneity artifact in spiral hyperpolarized 13C imaging of the human heart. Issue 1 (5th February 2021) - Reed, Galen D.; Ma, Junjie; Park, Jae Mo; Schulte, Rolf F.; Harrison, Crystal E.; Chen, Albert P.; Pena, Salvador; Baxter, Jeannie; Derner, Kelly; Tai, Maida; Raza, Jaffar; Liticker, Jeff; et al.
Abstract : Purpose: This study aimed to investigate the role of regional f 0 inhomogeneity in spiral hyperpolarized 13 C image quality and to develop measures to alleviate these effects. Methods: Field map correction of hyperpolarized 13 C cardiac imaging using spiral readouts was evaluated in healthy subjects. Spiral readouts with differing duration (26 and 45 ms) but similar resolution were compared with respect to off‐resonance performance and image quality. An f 0 map‐based image correction based on the multifrequency interpolation (MFI) method was implemented and compared to correction using a global frequency shift alone. Estimation of an unknown frequency shift was performed by maximizing a sharpness objective based on the Sobel variance. The apparent full width half at maximum (FWHM) of the myocardial wall on [ 13 C]bicarbonate was used to estimate blur. Results: Mean myocardial wall FWHM measurements were unchanged with the short readout pre‐correction (14.1 ± 2.9 mm) and post‐MFI correction (14.1 ± 3.4 mm), but significantly decreased in the long waveform (20.6 ± 6.6 mm uncorrected, 17.7 ± 7.0 corrected, P = .007). Bicarbonate signal‐to‐noise ratio ( SNR ) of the images acquired with the long waveform were increased by 1.4 ± 0.3 compared to those acquired with the short waveform (predicted 1.32). Improvement of image quality was observed for all metabolites with f 0 correction. Conclusions: f 0 ‐map correction reduced blur and recovered signal from dropouts, particularly along the posterior myocardial wall. The low image SNR of [ 13 C]bicarbonate can be compensated with longer duration readouts but at the expense of increased f 0 artifacts, which can be partially corrected for with the proposed methods.